Rapid Spread of Zika Virus in The Americas - Implications for Public Health Preparedness for Mass Gatherings at the 2016 Brazil Olympic Games. (March 2016) - Petersen, Eskild; Wilson, Mary E.; Touch, Sok; McCloskey, Brian; Mwaba, Peter; Bates, Matthew; Dar, Osman; Mattes, Frank; Kidd, Mike; Ippolito, Giuseppe; Azhar, Esam I.; Zumla, Alimuddin
Highlights: We discuss the global spread of the Zika virus (ZIKV) since its first discovery in 1947 in Uganda to the current outbreak in the Americas which has been declared a 'Global emergency' by the World Health Organization. We highlight that ZIKV and other arboviruses may pose a threat to the attendees of the 2016 Rio De Janeiro Olympic and Paralympic games and to residents of Brazil. We review clinical features and highlight the need for more accurate and rapid screening tests for ZIKV We discuss the recent possible linkage of microcephaly in babies exposed to ZIKV in utero, and highlight knowledge gaps in the epidemiology and pathogenesis of ZIKV. We review the public health implications of the current ZIKV outbreak and highlight the need for enhanced preparedness and proactive surveillance for all infectious diseases before, during and after the 2016 Olympic games. We stress that there is no specific treatment available or preventive vaccines and that that the emergence of ZIKV soon after the Ebola outbreak, is yet another wake up call for the urgent need for a coordinated global response for prevention and spread of infectious diseases with epidemic potential at mass gatherings events Summary: Mass gatherings at major international sporting events put millions of international travelers and local host-country residents at risk of acquiring infectious diseases, including locally endemic infectious diseases. The mosquito-borne Zika virus (ZIKV) has recently aroused global attention due to its rapid spread since its first detection in May 2015 in Brazil to 22 other countries and other territories in the Americas. The ZIKV outbreak in Brazil, has also been associated with a significant rise in the number of babies born with microcephaly and neurological disorders, and has been declared a 'Global Emergency by the World Health Organization. This explosive spread of ZIKV in Brazil poses challenges for public health preparedness and surveillance for the Olympics and Paralympics which are due to be held in Rio De Janeiro in August, 2016. We review the epidemiology and clinical features of the current ZIKV outbreak in Brazil, highlight knowledge gaps, and review the public health implications of the current ZIKV outbreak in the Americas. We highlight the urgent need for a coordinated collaborative response for prevention and spread of infectious diseases with epidemic potential at mass gatherings events.